Real Interpolation Method for Automatic Control Problems Solution - Goncharov V. I. Valery Ivanovich (Saarbrucken, LAP Lambert Academic Publishing, 2014)
Purpose of Real Interpolation Method for Automatic Control Problems Solution is to provide a ready reference to the Real Interpolation Method applications in the field of automatic-control systems design. Book is written by Prof.,Dr. Igor Aleksandrov (Tomsk State University), Prof.,Dr. Valery Goncharov (Tomsk Polytechnic University), A.Prof., Ph.D. Vladislav Rudnicki (Tomsk Polytechnic University), and A.Prof., Ph.D. Andrew Liepinsh (Tomsk Polytechnic University) on the basis of their lectures, practical works, courses for students, and also on the basis of the results obtained during some industrial design realizations. The authors hope this book will be a useful reference and a source of inspiration for all readers in this important field of automatic-control systems design.